2022
DOI: 10.1007/s11517-022-02632-x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of COVID-19 from tuberculosis and pneumonia using deep learning techniques

Abstract: Deep learning provides the healthcare industry with the ability to analyse data at exceptional speeds without compromising on accuracy. These techniques are applicable to healthcare domain for accurate and timely prediction. Convolutional neural network is a class of deep learning methods which has become dominant in various computer vision tasks and is attracting interest across a variety of domains, including radiology. Lung diseases such as tuberculosis (TB), bacterial and viral pneumonias, and COVID-19 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A CNN classification model for COVID-19 in pneumonia (including viral and bacterial infected CXR) was developed by Venkataramana et al [ 54 ]. In addition, by using their method, they were able to distinguish TB patients from CXRs that were contaminated with pneumonia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A CNN classification model for COVID-19 in pneumonia (including viral and bacterial infected CXR) was developed by Venkataramana et al [ 54 ]. In addition, by using their method, they were able to distinguish TB patients from CXRs that were contaminated with pneumonia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Venkataramana et al [29] proposed a multi-level classification system that contains two models. The first model is a binary classification model that classifies TB and pneumonia.…”
Section: Joint Diseases Detection Studiesmentioning
confidence: 99%
“…A summary of literature review is presented in Table 1 containing studies employed for multiple/joint disease detection from chest X-ray images. The highest average accuracy achieved in the validation phase for multiple disease is obtained by [29] as 96.6% with SMOTE and deep learning as a four-class problem. Nonetheless, as far as the binary classification problems are concerned, the highest accuracy achieved by [34] was 98.54%.…”
Section: Joint Diseases Detection Studiesmentioning
confidence: 99%
“…The fuzzy Colouring technique is used for pre-processing, then MobileNetV2 and SqueezeNet, are used for features extraction, and finally, Support Vector Machines (SVM) are used to classify images into three classes (normal, pneumonic, and COVID-19 positive) [1]. In COVID-Net, a deep 121-layer dense convolutional neural network [2] [5] and MobileNet architecture could automatically detect and extract the essential COVID-19, Pneumonia, and normal image features with 97.8% accuracy. Ozturk et al showed that DarkCovidNet (you only look once (YOLO), with seventeen convolutional layers), can be used to classify the Xray images in real-time into similar three classes (COVID-19, Pneumonia, and normal) with 87%, and two classes (COVID-19 and non-COVID-19) with 98.08% accuracy.…”
Section: Literature Surveymentioning
confidence: 99%
“…The severe symptoms are difficulty in breathing or shortness of breath [1], chest pain, loss of speech and mobility, etc. In extreme cases, COVID-19 mainly affects in lungs [2]. The damage to lungs, ARDS, Pneumonia, etc., are subsequent and life-threatening.…”
Section: Introductionmentioning
confidence: 99%